Plant-Derived Terpenes: A Feedstock for Specialty Biofuels. Issue 3 (March 2017) - Mewalal, Ritesh; Rai, Durgesh K.; Kainer, David; Chen, Feng; Külheim, Carsten; Peter, Gary F.; Tuskan, Gerald A.
Abstract : Research toward renewable and sustainable energy has identified specific terpenes capable of supplementing or replacing current petroleum-derived fuels. Despite being naturally produced and stored by many plants, there are few examples of commercial recovery of terpenes from plants because of low yields. Plant terpene biosynthesis is regulated at multiple levels, leading to wide variability in terpene content and chemistry. Advances in the plant molecular toolkit, including annotated genomes, high-throughput omics profiling, and genome editing, have begun to elucidate plant terpene metabolism, and such information is useful for bioengineering metabolic pathways for specific terpenes. We review here the status of terpenes as a specialty biofuel and discuss the potential of plants as a viable agronomic solution for future terpene-derived biofuels. Trends: Options for alternative non-petroleum-based transportation fuels are limited. Specific terpenes have the physical and chemical properties required for specialty biofuels capable of blending with or replacing petroleum-derived jet, missile, diesel, and gasoline fuels. Many plants naturally produce and store these specific terpenes. The biosynthesis of plant-derived terpenes is under strong genetic control. Strategies to increase terpene content are presented based on modern genetics and genomics approaches.